2022
DOI: 10.56946/jspae.v1i1.11
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Nitrogen, Zinc and Humic Acid Application on Wheat Growth, Morphological Traits, Yield and Yield Components

Abstract: To investigate the response of wheat to different levels of nitrogen (N), zinc (Zn) and humic acid (HA), an experiment was conducted at Agronomy Research Farm, the University of Agriculture, Peshawar, during 2014-15. The experiment was laid out in a randomized complete block design having three replications. Three levels of N (80, 120 and 160 kg ha-1), Zn (6, 12 and18 kg ha-1) and HA (5, 10 and 15 kg ha-1) were used. Results showed that N application at the rate of 160 kg ha-1 manifested maximum days to physio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…However, the plots where no foliar fertilization was applied remained lowest in spike length (7.0 cm). A recent study showed that 180 kg N, 18 kg Zn ha -1 combined with the application of 10 Kg humic acid gave a positive response in increasing the length of spikes of wheat crop (Iqbal et al, 2022). Farooqi et al, (2019) observed the highest 17.15 cm spike length when they treated their wheat crop with 8% N and 2% B foliar application.…”
Section: Spike Length (Cm)mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the plots where no foliar fertilization was applied remained lowest in spike length (7.0 cm). A recent study showed that 180 kg N, 18 kg Zn ha -1 combined with the application of 10 Kg humic acid gave a positive response in increasing the length of spikes of wheat crop (Iqbal et al, 2022). Farooqi et al, (2019) observed the highest 17.15 cm spike length when they treated their wheat crop with 8% N and 2% B foliar application.…”
Section: Spike Length (Cm)mentioning
confidence: 99%
“…The diminishing trend in wheat seed index was observed in rest of the treatments. However, the minimum seed index 38.0 g was observed in control treatment where no liquid N or Zn was applied Iqbal et al, (2022). conducted an experiment to evaluate the morphological traits, yield and yield components of wheat against numerous applications of nitrogen, zinc and humic acid.…”
mentioning
confidence: 99%
“…Micronutrients (zinc (Zn), iron (Fe), manganese (Mn), molybdenum (Mo), boron (B), copper (Cu) and chlorine (Cl)) improve plant health, water use efficiency, biomass production and provide systemic response against abiotic stresses [ 217 , 218 , 219 ]. Whereas plant growth-promoting rhizobacteria (PGPR) promote plant growth and tolerance to abiotic stresses by adapting and altering certain mechanisms, the production of ACC (1-aminocyclopropane-1-carboxylate) deaminase reduces ethylene synthesis, as well as alters phytohormones and antioxidative enzymes synthesis, and improves nutrient uptake [ 115 , 220 ].…”
Section: Plant Nutrition To Mitigate Adverse Effects Of Abiotic Stres...mentioning
confidence: 99%
“…N application level also significantly affected the yield composition factors ( Iqbal et al., 2022 ). One study showed that the number of bolls per unit area and the weight of a single boll of cotton decreased when the N application rate exceeded 280 kg/hm 2 on sandy loam ( Li et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%